Compromised Neurocircuitry in Chronic Blast‐Related Mild Traumatic Brain Injury - Yeh, Ping‐Hong (Hum Brain Mapp, 2016)
The aim of this study was to apply recently developed automated fiber segmentation and quantification methods using diffusion tensor imaging (DTI) and DTI‐based deterministic and probabilistic tractography to access local and global diffusion changes in blast‐induced mild traumatic brain injury (bmTBI). Two hundred and two (202) male active US service members who reported persistent post‐concussion symptoms for more than 6 months after injury were recruited. An additional forty (40) male military controls were included for comparison. DTI results were examined in relation to post‐concussion and post‐traumatic stress disorder (PTSD) symptoms. No significant group difference in DTI metrics was found using voxel‐wise analysis. However, group comparison using tract profile analysis and tract specific analysis, as well as single subject analysis using tract profile analysis revealed the most prominent white matter microstructural injury in chronic bmTBI patients over the frontal fiber tracts, that is, the front‐limbic projection fibers (cingulum bundle, uncinate fasciculus), the fronto‐parieto‐temporal association fibers (superior longitudinal fasciculus), and the fronto‐striatal pathways (anterior thalamic radiation). Effects were noted to be sensitive to the number of previous blast exposures, with a negative association between fractional anisotropy (FA) and time since most severe blast exposure in a subset of the multiple blast‐exposed group. However, these patterns were not observed in the subgroups classified using macrostructural changes (T2 white matter hyperintensities). Moreover, post‐concussion symptoms and PTSD symptoms, as well as neuropsychological function were associated with low FA in the major nodes of compromised neurocircuitry. Hum Brain Mapp 38:352–369, 2017. © 2016 Wiley Periodicals, Inc.